2020
DOI: 10.1371/journal.pgen.1008582
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Candida albicans Mig1 and Mig2 in glucose repression, pathogenicity traits, and SNF1 essentiality

Abstract: Metabolic adaptation is linked to the ability of the opportunistic pathogen Candida albicans to colonize and cause infection in diverse host tissues. One way that C. albicans controls its metabolism is through the glucose repression pathway, where expression of alternative carbon source utilization genes is repressed in the presence of its preferred carbon source, glucose. Here we carry out genetic and gene expression studies that identify transcription factors Mig1 and Mig2 as mediators of glucose repression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 64 publications
4
75
0
Order By: Relevance
“…Essentiality depends on the genetic background, and one caveat is that suppressor mutations may allow growth of cells lacking a normally essential gene. This has recently been reported also for SNF1, which could be deleted in strains that lacked the repressor Mig1 (16). In principle, it is possible that our snf1Δ mutants had acquired such a suppressor mutation after the induced gene deletion to allow visible colony formation within 2 to 3 days.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Essentiality depends on the genetic background, and one caveat is that suppressor mutations may allow growth of cells lacking a normally essential gene. This has recently been reported also for SNF1, which could be deleted in strains that lacked the repressor Mig1 (16). In principle, it is possible that our snf1Δ mutants had acquired such a suppressor mutation after the induced gene deletion to allow visible colony formation within 2 to 3 days.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, Lagree et al reported that SNF1 could be deleted in mutants lacking the repressor Mig1, indicating that unrestricted repression of Mig1 target genes in the absence of Snf1 explains the presumed essentiality of Snf1 ( 16 ). In our lab, we had also investigated the role of Mig1 in the regulatory network controlled by the SNF1 complex and deleted MIG1 as well as both MIG1 and the functionally related MIG2 in our snf4 Δ mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The data represent the average of two independent experiments. (Sexton et al, 2007;Lagree et al, 2020). In fact, deletion of HXK2 increased the expression of glucose transporter genes HGT7, HGT12, and HXT10 (Laurian et al, 2019).…”
Section: Deletion Of Hxk1 or Hxk2 Results In An Increased Glucose Tramentioning
confidence: 96%
“…The central carbon metabolism also plays pivotal roles in C. albicans pathogenicity, since a clear link between carbon control and pathogenicity is observed (Magalhães et al, 2017;Thammahong et al, 2017;Van Ende et al, 2019;Lagree et al, 2020). For example, it is shown that the amount of trehalose in the cells has an effect on filamentation (Serneels et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation